Study on the mechanism of anchoring parameters of anchor rods in cemented broken surrounding rock - Heng Ren; Yongjian Zhu; Qi Yao; Peng Li; Mingxing Wei (Scientific Reports)
Abstract In view of the difficulty of rock mass crushing and support on the surface of deep soft rock roadway with high stress, RMT-150 C rock mechanics experiment system was used to carry out the orthogonal test for sensitivity analysis of rock bolt support parameters of cemented broken rock mass. Through numerical simulation, the relationship between bolt parameters and the form and range of the formed compressive stress field was studied. The evolution law of interfacial shear stress in the anchorage section at the stage of elastic deformation is obtained. The results show that the main factors affecting the compressive strength of anchor solid are the number of anchor rods per unit area, followed by the presence or absence of anchor net, the anchor depth ratio, and the diameter of anchor rods. Increasing the anchorage length and diameter of the bolt is beneficial to improving the shear strength reserve of the bolt; The length of bolt affects the superposition range of axial compressive stress zone, the spacing of bolt affects the superposition range of radial compressive stress zone, and the diameter of bolt has little effect on the superposition range of compressive stress zone. The longer the length of bolt and the larger the spacing, the smaller the superposition range of compressive stress zone, or even disappear. The prestressing of bolt can make up for the supporting defects caused by long length and large spacing. The larger the prestressing is, the shape of compressive stress zone changes from “peanut shape” to “pomegranate shape”, and the active supporting effect becomes better gradually. The research results have reference significance for the selection of engineering bolt supporting parameters.